A Clinicopathological Appraisal of Port-site Infections after Laparoscopic Cholecystectomy: Our Experience at Shaheed Suhrawardy Medical College Hospital (Journal of Shaheed Suhrawardy Medical College, 2022)
Background: Undoubtedly the port site infections have remarkably enhanced to be a stigma as post laparoscopic morbidity and is still a field of debate and further exploration to surgeons. These port site infections (PSI) are infrequent surgical site infection, complicating the recovery of patients undergoing laparoscopic cholecystectomy. Hence, the necessity of further evaluation of the regarded facts was intended to be explored.Aim: This study was aimed to evaluate the factors that created or provoked PSI after laparoscopic removals of gall-bladder and at analysing which of these factors can be traced and modified to combat PSI in a trail to conquer these complications and to achieve maximum advantages from laparoscopic surgeries.Methods: A prospective descriptive qualitative study conducted on patients who underwent laparoscopic cholecystectomies in our hospital as well as at other facilities remote from our work stations. Factors as gender, site of infected port, types of microorganism, acuteness versus chronicity of the disease, types of infection (superficial or deep infection) and intraoperative spillage of stones, bile or pus were analysed in our study. Swabs were taken for culture and sensitivity tests in all patients who developed infections. Explorations were done under GA for some patients who had deep surgical site infections and wound debridement was done, excisional biopsies were taken for histopathological studies, and tissue samples for Gene-Xpert analysis for detection of Mycobacterium tuberculosis was done. All patients were followed up for six months postoperatively at our surgery unit rooms.Results: Port site infection rate was recorded in 40 cases amongst 340 procedures from the July 2018 to June 2020 (11.76%). A higher rate was observed in female patients 32 cases (9.41%) and 13 cases (3.82%) of acute cholecystitis. Larger number of cases of the PSI were superficial infections (77.5%) with non-specific microorganism in 34 cases (80.0%).Conclusion: We reconciled a significant association of PSI with spillage of bile or stones during the procedure and with acute cholecystitis. Most of the infections are superficial and more common in males. Precautions and protocols should be taken in measure to avoid unnecessary hurry and faulty procedure of sterilization during and prior to the whole surgery to combat PSI effectively.J Shaheed Suhrawardy Med Coll 2020; 12(2): 76-81